2019
DOI: 10.1002/adma.201808341
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Carbon Nanotube Confined Co–Nx Sites for Selective Hydrogenation of Biomass‐Derived Compounds

Abstract: Biomass is the most abundant renewable resource on earth and developing high‐performance nonprecious selective hydrogenation (SH) catalysts will enable the use of biomass to replace rapidly diminishing fossil resources. This work utilizes ZIF‐67‐derived nitrogen‐doped carbon nanotubes to confine Co nanoparticles (NPs) with Co–Nx active sites as a high‐performance SH catalyst. The confined Co NPs with Co–Nx exhibit excellent catalytic activity, selectivity, and stability toward a wide range of biomass‐derived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 29 publications
0
96
0
Order By: Relevance
“…The nearly absent appearance of a pre-edge feature (arisen from the forbidden 1s-to-3d transition) at~7709 eV in the CoN@CNTs indicates a symmetric coordination environment of Co, e.g., Co-N 4 32 . Notably, the Fourier transformed (FT) Co K-edge EXAFS spectra exhibit the signal of light scattering nearest neighbors at~1.5 Å, corresponding to the Co-N/C scattering pair 33,34 and further corroborating the existence of tetrahedrally coordinated Co (e.g., Co-N 4 ) 35,36 as revealed by fitting analysis (Supplementary Table 1). The weak signals originated from the Co-Co scattering path in a metallic feature might be ascribed to the rare appearance of Co nanoparticles.…”
Section: Resultsmentioning
confidence: 54%
“…The nearly absent appearance of a pre-edge feature (arisen from the forbidden 1s-to-3d transition) at~7709 eV in the CoN@CNTs indicates a symmetric coordination environment of Co, e.g., Co-N 4 32 . Notably, the Fourier transformed (FT) Co K-edge EXAFS spectra exhibit the signal of light scattering nearest neighbors at~1.5 Å, corresponding to the Co-N/C scattering pair 33,34 and further corroborating the existence of tetrahedrally coordinated Co (e.g., Co-N 4 ) 35,36 as revealed by fitting analysis (Supplementary Table 1). The weak signals originated from the Co-Co scattering path in a metallic feature might be ascribed to the rare appearance of Co nanoparticles.…”
Section: Resultsmentioning
confidence: 54%
“…Third, given that some biological systems present interesting properties themselves, the direct use of such biomaterials in functional devices would be an eco‐friendly and efficient way to develop bioinspired technologies. Recently, researchers discovered that biological materials directly derived from natural species exhibited outstanding performances in various energy applications such as photocatalysis, electrocatalysis, and biomass conversion . However, the precise and advanced biotechnology required in this route turns to be another major challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Gong et al demonstrated laser-mediated regulation of metal single-atom sites ( Figures 4M-4Q). 65 First, the carbon nanopolyhedrons made of CNTs ( Figures 4M and 4N) with abundant Co single-atom sites were prepared by a facile pyrolysis method, 72 via which a large number of these sites were deeply confined within the CNTs. The existence of Co single-atom sites is confirmed by the AC-STEM observation ( Figure 4N) and Co K-edge X-ray absorption near-edge structure (XANES) spectra ( Figure 4Q).…”
Section: Reviewmentioning
confidence: 99%